Distribute 2 to x and -2, and -6 to x and -2
2(x - 2) = 2x - 4
-6(x - 2) = -6x + 12
2x - 4 = 4x - 6x + 12
Simplify. Combine like terms
2x - 4 = (4x - 6x) + 12
2x - 4 = -2x + 12
Isolate the x. Add 4 to both sides, and 2x to both sides
2x (+2x) - 4 (+4) = -2x (+2x) + 12 (+4)
2x + 2x = 12 + 4
Simplify
4x = 16
Isolate the x. Divide 4 from both sides
4x/4 = 16/4
x = 16/4
x = 4
4 is your answer for x.
hope this helps
There is a mistake 9,12,13 is not a right triangle. but 9,12,15 is. IF you use this triangle instead, then the area of the 13,14,15 triangle is the sum of the area of the other two triangles.
C because eof plus fob will end up being 180
It would be 62+23=94 because you'll need to add the tens and the ones, then add it up
I think-_-